Dreaming in the contact zone: Zulu dreams, visions, and religion in nineteenth-century South Africa - Chidester, David (Journal of the American Academy of Religion, 2008)
In "Primitive Culture" (1871), E. B. Tylor supported his theory of religion, animism, by referring to reports about "savage" dreams. Citing Henry Callaway's "Religious System of the Amazulu" (1868-1870), Tylor invoked the dreams of a Zulu diviner, a "professional seer" who becomes a "house of dreams," as a classic example of animism because "phantoms are continually coming to talk to him in his sleep." In the original account, however, these spirits were not coming "to talk" to the diviner. They were coming to kill him. By situating nineteenth-century Zulu dreams and visions in a colonial contact zone of transcultural relations and asymmetrical power relations, we find a hermeneutics of dreams dealing with indeterminacy, an energetics of dreams, linking dreams to ancestral ritual, which is radically disrupted, and a new interreligious space of resources and strategies for negotiaing and navigating within a violent world.
free
Keywords: Callaway; Henry; Bp; 1817-1890; Christianity and African religions; Colonialism and neocolonialism; Culture and religion; Divination; Dreams – Religious aspects – African religion; Great Britain – Colonies – Africa; Hermeneutics; South Africa – Religion; South Africa.; Zulu (African people)